2019
DOI: 10.1016/j.ccep.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Idiopathic Ventricular Fibrillation and J-Wave Syndromes

Abstract: Idiopathic ventricular fibrillation (IVF) is defined as unexplained sudden cardiac death due to ventricular fibrillation (VF) without any identifiable structural or electrical cause after extensive investigations (no phenotype). Recent data show that the use of high-density electrophysiologic mapping may ultimately offer subclinical diagnoses of cardiac disease in about 90% of individuals with IVF. Two major conditions underlie the occurrence of VF: the presence of either depolarization abnormalities due to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Recent evidence shows, through high density electrogram mapping, a wide spectrum of heterogeneous substrates, which may be a consequence of late depolarization or caused by abnormalities in the ER: the first one due to microstructural changes not visible on CMR, and in the second due to a voltage gradient across the ventricular wall, in which case the Purkinje system has an important triggering role 6 . In both cases, the resulting substrate could be the cause of SMVT with a focal mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence shows, through high density electrogram mapping, a wide spectrum of heterogeneous substrates, which may be a consequence of late depolarization or caused by abnormalities in the ER: the first one due to microstructural changes not visible on CMR, and in the second due to a voltage gradient across the ventricular wall, in which case the Purkinje system has an important triggering role 6 . In both cases, the resulting substrate could be the cause of SMVT with a focal mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the resulting substrate could be the cause of SMVT with a focal mechanism. Current evidence shows ablation as a therapeutic option with favorable results 6 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that "idiopathic VF" may be less associated with a completely structurally normal heart than previously appreciated, which is compatible with the significant subset of IVF patients having localized structural alterations demonstrated by detailed endocardial and epicardial mapping. 4,17…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we firstly report a case that radiofrequency ablation for VF‐triggering PVCs originating from the tricuspid annular area successfully suppressed the recurrence of VF in a patient with ER syndrome. Recent studies demonstrated that J wave is related to ER abnormalities or delayed depolarization owing to microstructural alterations (Haissaguerre, Nademanee, Hocini, Duchateau, et al., 2019). In this case, the abnormal electrograms related to microstructural alterations were not recorded in the endocardium of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%